Self-efficacy of Teachers in Teaching English amid the Covid-19 Pandemic - Aulia Rahma Eka Kusuma Dewi; Diah Kristina; Ngadiso Ngadiso (STAI Hubbulwathan Duri, 2022)
This study aimed to analyze teachers’ self-efficacy in teaching English as a Foreign Language (EFL) amid the Covid-19 pandemic in Cilacap, Central Java province, Indonesia. The study used a qualitative case study design. This study had exposed the questionnaire from twelve teachers in three Senior High Schools and interviewed four teachers from each of these three schools as the represented respondents. The data were then analyzed using the interactive model of data analysis. Moreover, the responses for the self-efficacy scale revealed the result of the percentage used to conclude and the interview result usage to support the teachers’ perception of their self-efficacy in teaching English. The result proved that these teachers possess a high self-efficacy in teaching EFL. These teachers delivered positive responses and perceptions of their high self-efficacy, which encouraged them to have a great deal of determining instructional strategies, engaging the students, and managing the class during distance learning. Furthermore, specific findings within the domains of instructional strategies, student engagement, and classroom management provide further insight into the importance of examining the overall self-efficacy of EFL teachers in supporting distance learning.